Prevalence of cardiovascular-related comorbidity in ankylosing spondylitis, psoriatic arthritis and psoriasis in primary care: a matched retrospective cohort study. Issue 12 (December 2016) - Ahmed, Nadeem; Prior, James; Chen, Ying; Hayward, Richard; Mallen, Christian; Hider, Samantha
Abstract The aim of this study is to compare the prevalence of cardiovascular (CVD)-related comorbidities in patients with ankylosing spondylitis (AS), psoriatic arthritis (PsA) or psoriasis (Ps) in UK primary care against matched cohorts. Matched retrospective cohort study used a primary care consultation database. Three cohorts were constructed using all patients with a Read code diagnosis of AS, PsA or Ps between 1999 and 2009; each cohort was then compared in a 1:4 ratio to a matched cohort. The prevalence of CVD-related comorbidities (hypertension, ischaemic heart disease, hyperlipidaemia and diabetes mellitus) were identified by the first consultation of a comorbid Read code, in those with an inflammatory condition of interest. The prevalence of CVD-related comorbidities was compared between each inflammatory cohort and their matched cohort using Fisher's exact test. Ninety-four AS, 106 PsA and 290 Ps patients were identified. Compared with matched cohorts, the most prevalent CVD-related comorbidity in patients with AS was hypertension (35 (37.2 %) vs. 96 matched (25.5 %), p = 0.03); this was also the case for PsA (41 (38.7 %) vs. 114 matched (26.9 %), p = 0.02). No differences were seen in the prevalence of other CVD-related comorbidities in those with AS, PsA or Ps compared to their matched cohorts. Our findings provide UK comparisons of CVD-related comorbidities in patients with AS, PsA and Ps alone; specifically, demonstrating increased prevalence of hypertension in AS and PsA cohorts compared to their matched cohorts. This further supports the argument for more evidence in the need for screening and intervention around CVD comorbidities in inflammatory conditions.